Schlieren visualization of fluid dynamics effects in direct analysis in real time mass spectrometry. (28th January 2015) - Curtis, Matthew; Keelor, Joel D.; Jones, Christina M.; Pittman, Jennifer J.; Jones, Patrick R.; Sparkman, O. David; Fernández, Facundo M.
Abstract : Rationale: The success of ambient analysis using plasma‐based ion sources depends heavily on fluid dynamics and mass transport efficiency in the sample region. To help characterize the influence of these determining factors, visualization of the gas flow profile for a Direct Analysis in Real Time (DART) ion source at the mass spectrometer atmospheric pressure (AP) interface was performed using the Schlieren technique. Methods: The DART helium flow pattern was imaged in model systems incorporating different interface designs, i.e. skimmer or capillary inlet, and for sampling strategies using several types of traditional DART sample probes including a glass capillary, swab, and drug tablet. Notably, Schlieren experiments were conducted on instruments equipped with the gas‐ion separator tube (GIST) adapter and Vapur® pump, and on setups featuring the transmission mode (TM) DART module used in standard practice. Results: DART sources were seen to expel a collimated, highly laminar helium stream across interface distances up to 8 cm. The helium stream was robust to the influence of gas temperature (50–500 °C) and flow rate (≤3.5 L min –1 ), but considerable DART gas deflection or full disruption was observed in each sampling scenario. The severity of the flow disturbance depended on probe size and placement, the GIST/Vapur® settings, or counter‐current gas movements present at the interface. Conclusions: The real‐time Schlieren visualizations introduced in this work provide new insight on the fluid dynamics within the DART‐MS sample gap while also helping to identify those experimental parameters requiring optimization for improved transmission. Copyright © 2015 John Wiley & Sons, Ltd.